PENGGUNAAN IMPLAN PADA ZIGOMA UNTUK REHABILITASI PASCA MASILEKTOMI SEBAGIAN: ZYGOMA IMPLANT-SUPPORTED PROSTHETIC REHABILITATION AFTER PARTIAL MAXILLECTOMY - Eddy Anwar Ketaren; Nelly (Dentika: Dental Journal, 2010)
Patients with severe maxillary defects have major difficulties to re-establish their mastication, speaking, soft tissue projection and social intergration. The reconstruction of maxilla defect after tumor resection continues to pose a challenge for the reconstructive oral and maxillofacial surgeon. The zygomatic implant, which was introduced in recent years, can offer a valuable alternative to extensive augmentation procedures. The zygomatic implant represents such a development and is inadequate alveolar bone for placing sufficient dental implants. The goal of using the zygoma as an implant anchoring site was to provide predictable posterior anchorage for restoring dentist’s prosthetic efforts. As conclusion, zygoma implant decrease defect, increase maintainance, reconstruct maxilla caused of tumor resection or trauma, where the main aims is to return the effort of abturator prosthetic procedure.